1964
DOI: 10.1139/v64-114
|View full text |Cite
|
Sign up to set email alerts
|

The Photolysis of Water Vapor and Reactions of Hydroxyl Radicals

Abstract: The photolysis of water vapor a t 1849 A has been investigated as a possible source of hydroxyl radicals for kinetic studies. At temperatures from 23 to 350' C and pressures from 1.3 t o 28 mm, H2 and H402 were the only detectable products. Experiments with added oxygen indicated that 0 2 ma37 have been present as a n intermediate a t a very low steady-state concentration, although this is not certain. Possible mechanisms are discussed. Ea2 -E C O = 4.0Zk0.3 kcal/mole, AH,/Aco = 3 1 f 5 , At temperatures below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

1971
1971
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 14 publications
0
26
1
Order By: Relevance
“…However, Smith and Zellner [4] failed to observe any rate enhancement for O H removal, even a t 250 torr He. Ung and Back [8] in a competitive study with H2 at 250 torr total pressure (mostly Hz) found k2/kl to be somewhat greater than the present consensus value for this ratio.…”
Section: Introductioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, Smith and Zellner [4] failed to observe any rate enhancement for O H removal, even a t 250 torr He. Ung and Back [8] in a competitive study with H2 at 250 torr total pressure (mostly Hz) found k2/kl to be somewhat greater than the present consensus value for this ratio.…”
Section: Introductioncontrasting
confidence: 68%
“…where a: is a small correction factor due to reactions (4) and (6) The effect due to reaction (5) was neglected because it is very small (<5Y0) and is further reduced because of reactions (7) and (8). a can be computed from the known rate coefficients given in Figure 1, and at 250°K and a single total pressure of about 600 torr in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…In 1974 it was reported [57], and later confirmed by both indirect [58][59][60] and direct measurements [61,62], that the rate constant at ambient temperatures increases with total pressure, although indications of a potential pressure dependence could be inferred from an early competitive study of Ung and Back [63]. It was also established that various gases have different efficiencies in increasing the rate constant; SF6 is very efficient whereas He and Ar have little or no effect [61,62].…”
Section: A Oh+co ~ H+co2mentioning
confidence: 97%
“…(7) → (6)). 12 H2O + hν → ·H + ·OH (7) The excitation wavelength is 200 nm or shorter. Although light beams of such short wavelengths were mostly cut off by the cold mirror, the photolysis might have been driven by stray UV light.…”
Section: Generation Of H2o2 In the Absence Of Tio2mentioning
confidence: 99%